Faktor-Faktor yang Memengaruhi Keputusan Petani Untuk Berkontribusi pada Kemitraan Closed Loop Agribisnis di Kabupaten Garut - Erawan, Wahid; Awaliyah, Fitri; Mustaqiem, Ashrul Fadlil (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
From 2019 to 2022, Indonesia has faced uncertainty in the economic sector as a result of the COVID 19 pandemic. To accelerate the handling of post-pandemic national economic recovery, one of them is the Closed Loop inclusive partnership program. The aim of this research is to describe partnership patterns and identify what factors influence farmers' decisions to contribute to Closed Loop agribusiness partnerships in Garut Regency. The research was conducted in 3 subdistricts namely Cikajang, Cigedug, and Cisurupan as locations for agribusiness Closed Loop pilot projects. This research is a quantitative research. The sampling technique used was a census of 50 partner farmers, data were collected using interview techniques. The analytical method used is descriptive analysis and multiple linear regression analysis using SPSS version 23 software. The results of the research show that the partnership pattern implemented in the Closed Loop agribusiness program involves several multi-stakeholders including the government, companies providing agricultural production facilities, banking, farmers, the Eptilu Cooperative, extension workers and off takers who have a role in providing access to capital, market guarantees, providing production facilities and extension services, as well as updating technology for farmers. There are several factors that have a significant influence on farmers' decisions to partner, namely the Closed Loop program providing market guarantees and price certainty, access to capital and access to production facilities and counseling which are felt to really help farmers in increasing their capacity and capability.